Fortification of Moringa Leaves to Fulfill the Nutritional Needs of Stunting Toddler (International Journal of Scientific Research and Management (IJSRM), 2023)
Nutritional problems are a classic health problem that recurs every year, especially in developed countries and including Indonesia. One of the nutritional problems faced by Indonesia is that there are still stunting cases experienced by toddlers. The problem of stunting is a hotly discussed issue considering that the impact of stunting incidents that are not immediately addressed can have an impact on reducing the quality of life of Indonesian people. The culture of parents to prepare food according to what they consume for stunted toddlers and not to worry about the toddler’s short height are two problems that cause stunting in Indonesia. One effort that can be made to overcome the problem of stunting is to ensure that stunted toddlers have a good appetite. When a stunted toddler’s appetite increases, the problem of stunting will soon be resolved properly. The aim of this study was to analyze the effectiveness of giving churros made using Moringa leaf flour to increase the height of stunted toddlers. The research design used was pre-experimental. The samples in this study were taken from three working areas of the public health unit in Sooko District, Gondang District and Jatirejo District. The variable studied was the toddler’s height. Data analysis tests were carried out using the Mann-Whitney test. From the results of the Mann-Whitney test, a significance value of 0.022 < 0.05 was obtained, so it can be concluded that giving churros made using Moringa leaf flour is effective in increasing height in stunted toddlers